The Effectiveness of Web-Based Education Women Health (E-WoHealth) on The Level of Skills of Pregnant Women About Breast Care - Anggraeni, Ni Made Dewi; Ahmad, Mardiana; Baso, Yusring Sanusi; Jusuf, Elizabeth C.; Rafiah, Sitti; Nurdin, Jibril (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
The report from the Bone Bolango District Health Office shows that the prevalence of exclusive breastfeeding for the last 3 years has decreased, namely in 2019 by 28.3%, in 2020 by 16%, and in 2021 it has decreased by 12.7%. Many factors cause the low rate of exclusive breastfeeding in children, one of which is caused by poor knowledge about breastfeeding. Based on these problems, media is needed to increase the skills of pregnant women regarding breast care. This research aims to create a web platform called E-WoHealth which can improve pregnant women's skills regarding breast care. This research used Research and Development (R&D) methods. Then to see the difference before and after the use of Web-based E- WoHealth on the skill level of pregnant women in performing breast care using the Pre-Experimental Design (One group pretest-posttest design). This study was carried out in the working area of the Kabila Health Center, Oluhuta, Kec. Kabila, Bone Bolango Regency, Gorontalo. Population in research tian namely third-trimester pregnant women in the working area of the Kabila Health Center, Bone Bolango Regency, as many as 60. Data collection techniques, documentation, questionnaires, tests, and observations. The results showed that the results of the web-based E-WoHealth feasibility test were in the very feasible category, and the statistical test results showed that the web-based E-WoHealth was effective in increasing pregnant women's skill regarding breast care with a p-value of 0.000 (p<0.05). Thus, education on breast care using web-based E-WoHealth is feasible and effective in increasing the skills of pregnant women before and after the intervention. It is hoped that the health office can socialize this platform with pregnant women to raise awareness about breast care.